Comprehensive assessment of the aortic valve in critically ill patients for the non-cardiologist. Part I: Aortic stenosis of the native valve - Walpot, Jeroen; Vermeiren, Guy L.; Al Mafragi, Amar; L.N.G. Malbrain, Manu (Anestezjologia Intensywna Terapia, 2021)
Aortic stenosis (AS) causes left ventricular outflow obstruction. Severe AS has major haemodynamic implications in critically ill patients, in whom increased cardiac output and oxygen delivery are often required. Transthoracic echocardiography (TTE) plays a key role in the AS severity grading. In this review, we will give an overview of how to use the simplified Bernoulli equation to convert the echo Doppler measured velocities (cm s-1) to AS peak and mean gradient (mm Hg) and how to calculate the aortic valve area (AVA), using the continuity equation, based on the principle of preservation of flow. TTE allows quantification of compensatory left ventricular (LV) hypertrophy, assessment of LV systolic function, and determination of LV diastolic function and LV loading. Subsequently, the obtained results from the TTE study need to be integrated to establish the AS severity grading. The pitfalls of echocardiographic AS severity assessment are explained, and how to deal with inconsistency between AVA and mean gradient. The contribution of transoesophageal echocardiography, low-dose dobutamine stress echo (in case of low-flow low-gradient AS), echocardiography strain imaging, cardiac magnetic resonance imaging, cardiac multidetector computed tomography and the relatively new concept of Flow Pressure Gradient Classification to the work-up for aortic stenosis is discussed. Finally, the treatment of AS is overviewed. Elective aortic valve replacement is indicated in patients with severe symptomatic AS. In the ICU, afterload reduction by vasodilator therapy and treatment of pulmonary and venous congestion by diuretics could be considered.